E Edukasi Literasi Digital Dalam Upaya Pencegahan Penipuan Dunia Maya (Cyberfraud) Bagi Masyarakat Desa Sungai Bangkal: Digital Literacy Education for Cyber Fraud Prevention in Sungai Bangkal Village Community - Fikri, Ahmad; Noor, Ade Surya Jaya; Zidan, Muhammad; Fatimah, Fatimah; Lena, Mahda; Ameliani, Eka; Ilmi, Jainal; Amnah, Amnah; Murniyati, Murniyati; Hasnah, Nor; Amin, Muhammad Nor (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2025)
The rapid surge in internet connectivity across Indonesia presents dual implications: enhanced information access and increased exposure to cybercrimes. Rural communities often become primary targets due to a significant digital literacy gap. This community service initiative aimed to fortify the residents of Sungai Bangkal Village, Banjar Regency, against cyberfraud threats through preventive education. Conducted under Kuliah Kerja Nyata (KKN) framework, the program utilized a social intervention approach combining face-to-face socialization with the distribution of practical guide brochures. Program effectiveness was measured through surveys on public understanding of various crime modes. The evaluation revealed a significant disparity in knowledge. While the vast majority (91%) recognized conventional phone scams, awareness regarding technical manipulation techniques such as phishing remained critically low at 28%. Demographically, the younger cohort (18-24 years) exhibited the highest vigilance, whereas residents over 45 were identified as the most vulnerable group. While this intervention successfully established a foundation for collective alertness, the findings suggest an urgent need for continuous digital mentoring to bridge the knowledge gap regarding more sophisticated cyber threats.